Technological innovation in New European Union Markets - Uzagalieva, Ainura (2019)
We analyze the role of innovation in the technological development of four new EU members: the Czech Republic, Hungary, Poland and Slovakia. For that purpose, we use a novel approach by modeling the empirical relationship between intra-industrial bilateral trade flows, which proxy the level of technological progress, and innovation expenditures within the context of a gravity model with a set of appropriate instrumental variables to account for the potential endogeneity of innovation to trade. We show that innovation efforts in high-tech industries exhibit a strong effect on the technological progress of the region and they are closely linked to foreign direct investment and multinationals. As foreign-owned subsidiaries become a part of the innovation systems and industrial structure of the host country they promote overall technological growth in the region.